2003
DOI: 10.1063/1.1586457
|View full text |Cite
|
Sign up to set email alerts
|

Subwavelength ripple formation on the surfaces of compound semiconductors irradiated with femtosecond laser pulses

Abstract: High-spatial-frequency periodic structures on the surfaces of InP, GaP, and GaAs have been observed after multiple-pulse femtosecond laser irradiation at wavelengths in the transparency regions of the respective solids. The periods of the structures are substantially shorter than the wavelengths of the incident laser fields in the bulk materials. In contrast, high-frequency structures were not observed for laser photon energies above the band gaps of the target materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
350
4
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 608 publications
(373 citation statements)
references
References 16 publications
14
350
4
5
Order By: Relevance
“…Ripples which are either orthogonal [7][8][9][10][11][12][13][14][15] or parallel [16][17][18][19] to the polarization, with a periodicity significantly smaller than the laser light, have been observed for laser pulse durations in the picosecond and femtosecond regime. These are often referred to as high spatial frequency LIPSSs (HSFLs), and as for LSFLs, they were observed on metals, 18,20 semiconductors, [7][8][9][10][11][12]16,17 and dielectrics as well. [13][14][15]19 The influence of polarization, angle of incidence, and wavelength of a laser beam on LSFL formation strongly indicates that the phenomenon is mainly governed by the electromagnetic field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ripples which are either orthogonal [7][8][9][10][11][12][13][14][15] or parallel [16][17][18][19] to the polarization, with a periodicity significantly smaller than the laser light, have been observed for laser pulse durations in the picosecond and femtosecond regime. These are often referred to as high spatial frequency LIPSSs (HSFLs), and as for LSFLs, they were observed on metals, 18,20 semiconductors, [7][8][9][10][11][12]16,17 and dielectrics as well. [13][14][15]19 The influence of polarization, angle of incidence, and wavelength of a laser beam on LSFL formation strongly indicates that the phenomenon is mainly governed by the electromagnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…The origin of HSFL is still under debate and several theories have been proposed to explain their formation, such as self-organization, 13,16 second-harmonic generation, 7,8,12 or the η theory extended with a modification of the optical properties. 12,19,23 It must be noted that the η theory was created to explain LIPSS formation at a time when HSFLs had not yet been observed.…”
Section: Introductionmentioning
confidence: 99%
“…1 So far, several mechanisms have been proposed to explain the formation of nanogratings induced by femtosecond laser pulses, such as interference between the incident laser light and the surface scattered wave [17], self-organization [6], second harmonic generation (SHG) [8], excitation of surface plasmon polaritons [18], and Coulomb explosion [19] etc. However, it is suggested from our research that the surface plasmon polaritons (SPPs) excited by femtosecond laser irradiation can explain the formation of nanogratings in this paper [20,21].…”
Section: Resultsmentioning
confidence: 99%
“…According to the periods of LIPSSs, the LIPSSs can be divided into two types [7,8]. While the LIPSSs with periods approximately equal to the laser wavelength are called low spatial frequency LIPSSs (LSFLs), the LIPSSs with periods much smaller than the laser wavelength are referred to as high spatial frequency LIPSSs (HSFLs).…”
Section: Introductionmentioning
confidence: 99%
“…The nanostructures using some beam processes such as electron [1,2], ion [3,4], molecular [5][6][7][8][9] and laser [10][11][12][13][14][15][16][17][18] was reported by their experimental observations. In particularly, a pulsed laser irradiation has been also achieved surface damage pattern at nanoscale on material surface with a wavelength-dependent periodicity by the interference of laser lights [19][20][21][22][23][24][25][26]. In addition, the experimental observations have revealed that nanosecond pulsed laser irradiation induced a self-organization due to the thermal effect [14][15][16].…”
Section: Introductionmentioning
confidence: 98%